Bankruptcy Moratorium Plan and Suspension of Debt Payment Obligations Reviewed From Legal Protection of Creditors - Serlika Aprita (Fakultas Hukum, Universitas Islam Bandung, 2022)
The formulation of a bankruptcy moratorium policy and Postponement of Debt Payment Obligations (PKPU) is not an urgent matter to be enacted in the form of a Perppu because it has been regulated in Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. If this policy is enforced, then legally the legal authority for the application for filing for bankruptcy and the application for Postponement of Debt Payment Obligations (PKPU) is in the hands of the Government. And the tendency of this which initially aims to provide opportunities for debtors to be able to resolve debt problems within a certain period of time will actually lead to losses experienced by other parties, such as the banking industry. It is not only a loss, but this pattern also leads the interested parties to use this as a momentum to benefit themselves through the moral hazard mode.